Strategi Pemasaran Syariah dalam Upaya Meningkatkan Penjualan Sate Madura (Studi Pada warung sate Madura Cak Budi dijalan Imam Bonjol Kota Metro - Muhammad Aldo; Ria Sulistiani; Lilis Renfiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Marketing management strategy is a process that allows an organization or company to explore large market opportunities, increase sales, and achieve the desired level of profit. The importance of marketing management strategy also lies in its role as a vital tool in securing the company's position in business competition. The main goal of marketing is to carry out transactions, provide services, fulfill needs, and accommodate customer desires to ensure their satisfaction. The marketing function primarily involves product development. If there is a decline in the acceptance of products in circulation, additional steps in product development are needed to suit the dynamics of business development. In the context of the problems faced, the author focuses on two main problems: 1) how marketing management strategies can increase sales at the Sate Madura Cak Budi stall on Jalan Imam Bonjol and Cak Umar on Jalan Soekarno Hatta, 2) what factors support or hampering marketing management strategies in increasing sales at the two stalls. This research adopts qualitative research methods using observation, interviews and documentation as data collection techniques. The main objective is to provide a detailed and structured explanation about the implementation of sharia marketing management strategies to increase sales at the Sate Madura stalls Cak Budi and Cak Umar. These two stalls apply a sharia marketing approach using the 4P marketing mix concept (product, price, promotion, place). The main supporting factors for this strategy are strategic locations that are easily accessible to consumers and communication strategies aimed at attracting customers from outside the Metro City area. However, the main obstacle for the Sate Cak Budi and Cak Umar stalls is the fairly tight competitive situation in the Metro City area.